2017
DOI: 10.1089/apc.2017.0124
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Healthcare Environment and Associations with Clinical Outcomes of People Living with HIV/AIDS

Abstract: Despite three decades of dramatic treatment breakthroughs in antiretroviral regimens, clinical outcomes for people living with HIV vary greatly. The HIV treatment cascade models the stages of care that people living with HIV go through toward the goal of viral suppression and demonstrates that <30% of those living with HIV/AIDS in the United States have met this goal. Although some research has focused on the ways that patient characteristics and patient-provider relationships contribute to clinical adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…To address the gap in the literature, the aim of this study was to describe provider approaches to engage patients into the HCC. Although the findings from this study support previous understandings about patient-provider interactions in health promotion, [22][23][24][25] contextualizing providers' experiences reveals the intricacies of specific approaches to address patient vulnerabilities. The provider narratives revealed that efforts and approaches aligned across disciplines indicating the influence of evidence-based practice in HIV prevention and treatment.…”
Section: Discussionsupporting
confidence: 59%
“…To address the gap in the literature, the aim of this study was to describe provider approaches to engage patients into the HCC. Although the findings from this study support previous understandings about patient-provider interactions in health promotion, [22][23][24][25] contextualizing providers' experiences reveals the intricacies of specific approaches to address patient vulnerabilities. The provider narratives revealed that efforts and approaches aligned across disciplines indicating the influence of evidence-based practice in HIV prevention and treatment.…”
Section: Discussionsupporting
confidence: 59%
“…Substance use is a common point of friction between participants and healthcare systems providers. PLWH who use substances or have done so in the past commonly experience, or anticipate they will experience, judgment from healthcare providers, which, they fear, may result in denial of care [60,61]. Indeed, these stigmatizing attitudes toward and substandard treatment of PLWH who use or are perceived to use substances is another form of symbolic violence.…”
Section: Internalization Of Symbolic Violencementioning
confidence: 99%
“…In fact, there is a substantial literature on symbolic violence and its effects on persons who use substances, as they are another population that is considered socially and culturally controlled [31]. However, HIV health care providers may not always have the skills to engage patients around substance use concerns, particularly in the context of a short health care encounter [60,61]. Nonetheless, substance use is an important juncture for PLWH where symbolic violence is communicated and potentially internalized, and which contributes to discontinuation of HIV care and ART.…”
Section: Internalization Of Symbolic Violencementioning
confidence: 99%
“…Of serious concern, PLWH commonly withdraw from HIV care altogether and stop taking ART as a means of exercising their autonomy and coping with negative affect inherent in these strained encounters. On the other hand, health care providers and the settings in which they operate are under pressure to bring all their patients onto ART and achieve viral suppression, even while health care encounters are short and resources may be insufficient (58). Further, health care providers may not have the training or resources to address the complex material, social, and psychological needs that PLWH from low SES backgrounds may experience (59).…”
Section: Discussionmentioning
confidence: 99%
“…PLWH who have used or who are currently using substances often experience judgement and potential denial of equitable health care from healthcare providers. However, HIV care providers are trained to treat this complex chronic health condition, and may not have the skills or interest in engaging patients around substance use concerns (58,60).Thus, substance use is another point of friction that commonly serve as a juncture when patients are lost from HIV care and/or stop taking ART. It must be noted, however, most participants report having numerous positive and even life-changing and life-saving experiences with their own personal healthcare providers.…”
Section: Discussionmentioning
confidence: 99%